The Effect of Using a Lattice Model to Estimate Reported Option Values - Bratten, Brian; Jennings, Ross; Schwab, Casey M. (Contemporary Accounting Research, 2015)
Abstract Statement of Financial Accounting Standards 123R suggests that lattice valuation models may improve the estimates of reported employee stock option values relative to the more commonly used Black–Scholes (BS) model. However, lattice model critics have expressed concerns that managers may use lattice models' flexibility to opportunistically understate option values. In this study, we investigate a sample of firms that recently adopted a lattice model to value employee stock options to provide evidence on this issue by identifying the determinants of lattice model adoption and examining the effect of lattice model use on reported option values. We report three main results. First, we find that firms are more likely to adopt a lattice model when it is more likely to produce lower values than the BS model and when managers have incentives to lower stock option expense. Second, we find that firms adopting a lattice model increase understatement of reported option values more than firms that continue to use the BS model and that the incremental understatement is due to use of the lattice model. Third, we conduct several tests to examine whether the valuation effect of lattice model use is consistent with efforts to correct for documented shortcomings in the BS model and find no evidence that this is the case. Taken together, the evidence in this study suggests that firms adopt and implement lattice models primarily to lower reported option values.